Moving in the Margins: Desert Travel and Power in Medieval Central Asia - Wordsworth, Paul D. (Asian Studies E-Books Online, Collection 2025., 2025)
Central Asia has been perceived as a landscape of connections, of Silk Roads; an endless plain across which waves of conquerors swiftly rode on horseback. In reality the region is highly fragmented and difficult to traverse, and overcoming these obstacles led to routes becoming associated with epic travel and high-value trade. Put simply, the inhabitants of these lands became experts in the art of travelling the margins. This volume seeks to unravel some of the myths of long-distance roads in Central Asia, using a desert case-study to put forward a new hypothesis for how medieval landscapes were controlled and manipulated.